Disease burden of bladder cancer in China and the different SDI regions over the world from 1990 to 2021 - Xiaosheng Chen; Hanbin Guo; Sizhe Cao; Jieming Lin; Peidong Huang; Wei Zhang; Huirong Lin; Xinji Li; Hui Zhang (Scientific Reports)
Abstract Bladder cancer is the most prevalent malignancies in the urinary system. This study was designed to investigate the trends of bladder cancer in China and differences compared with various Socio-demographic index (SDI) regions. Data from the Global Burden of Disease (GBD) 2021 database were utilized to evaluate metrics associated with bladder cancer, including age-standardized incidence rate (ASIR), age-standardized prevalence rate (ASPR), age-standardized mortality rate (ASMR), and age-standardized disability-adjusted life years rate (DALY) (ASDR). All analyses, including joinpoint regression, age-period-cohort, decomposition, spearman correlation, frontier and cross-country inequality, and Bayesian age-period-cohort, were utilized. In 2021, bladder cancer posed a significant health burden in China, with 570,636 total cases, including 463,364 males. The disease burden increased from low to high SDI regions, with China falling in the middle to high-middle SDI range. Apart from China, middle SDI and low-middle SDI regions, the ASIR of all other SDI regions showed a decreasing trend. The ASPR of bladder cancer increase globally, particularly in China and middle SDI region. Meanwhile, the ASMR and ASDR declined in China and all SDI regions. The age-period-cohort analysis showed that period and cohort effects influenced the ASIR and ASPR differently across China and each SDI region. Population growth was the primary driver of increases in these metrics. Projections suggest continued increases in ASIR, ASPR, and ASDR for both genders in China through 2036. The burden of bladder cancer is significant in China and varies across SDI regions, highlighting the link between socioeconomic development and disease burden.